Meta-analysis of cardiovascular outcome trials assessing the cardiovascular efficacy and safety of dipeptidyl peptidase-4 inhibitors in patients with type 2 diabetes mellitus. (14th October 2021) - Patoulias, D; Boulmpou, A; Teperikidis, E; Katsimardou, A; Siskos, F; Tranidou, A; Nikolaidis, A; Mouselimis, D; Doumas, M; Papadopoulos, C E; Vassilikos, V
Abstract: Background: Type 2 diabetes mellitus (T2DM) represents an independent risk factor for the development of cardiovascular disease, which accounts for half of deaths among the affected patients. Patients with T2DM experience higher incidence of vascular interventions compared to high-risk patients without T2DM or cardiovascular disease at baseline, underscoring the necessity for targeted therapeutic interventions. Dipeptidyl peptidase-4 (DPP-4) inhibitors constitute a safe treatment option with fair glycemic efficacy in T2DM whose cardiovascular efficacy has been doubted over recent years. A series of randomized controlled trials (RCTs) addressing cardiovascular outcomes with DPP-4 inhibitors have been recently published, while previous meta-analyses failed to show any cardiovascular benefit with their use in patients with T2DM. Purpose: The purpose of our analysis was to report the impact of antidiabetic treatment with DPP-4 inhibitors on different cardiovascular efficacy outcomes. Methods: We searched PubMed for all published RCTs assessing cardiovascular outcomes after antidiabetic treatment with DPP-4 inhibitors. We extracted data related to the following efficacy outcomes: fatal and non-fatal myocardial infarction, fatal and non-fatal stroke, hospitalization for heart failure, hospitalization for unstable angina, hospitalization for coronary revascularization and cardiovascular death. Results: We pooled data from a total of 6 trials in a total of 52, 520 patients. Antidiabetic treatment with DPP-4 inhibitors did not significantly affect any of the prespecified cardiovascular efficacy outcomes. More specifically, DPP-4 inhibitors compared to control led to a non-significant increase in the risk for fatal and non-fatal myocardial infarction (RR=1.02, 95% CI: 0.94–1.11, I 2 =0%), hospitalization for heart failure (RR=1.09, 95% CI: 0.92–1.29, I 2 =65%) and cardiovascular death (RR=1.02, 95% CI: 0.93–1.11, I 2 =0%), as shown in figures 1a, 1c and 1f. In addition, DPP-4 inhibitors produced a non-significant decrease in the risk for fatal and non-fatal stroke (RR=0.96, 95% CI: 0.85–1.08, I 2 =0%) and coronary revascularization (RR=0.99, 95% CI: 0.90–1.09, I 2 =0%), as depicted in figures 1b and 1e. Finally, DPP-4 inhibitors demonstrated a neutral effect on the risk for hospitalization due to unstable angina (RR=1.00, 95% CI: 0.85–1.18, I 2 =0%), as shown in figure 1d. Conclusions: Antidiabetic treatment with DPP-4 inhibitors does not seem to confer any significant cardiovascular benefit for patients with T2DM. FUNDunding Acknowledgement: Type of funding sources: None.